Analysis of the potential of rare earth elements in acid mine drainage and sedimentation pond sludge - Afrah, Bazlina Dawami; Iqbal, Muhammad; Payomthip, Panida; Farand, Muhammad Geo; Syabil, M. Ibnus (Journal of Degraded and Mining Lands Management, 2026)
Acid Mine Drainage (AMD) generated by coal mining is commonly regarded as an environmental liability, yet it may also serve as a secondary source of Rare Earth Elements (REEs). This study evaluated the distribution, classification, and recovery potential of REEs in AMD water and sedimentation pond sludge from a coal mining area in South Sumatera, Indonesia. Four AMD water samples were collected from different mine pits, while two sludge samples were obtained from the inlet and outlet of a sedimentation pond. REEs concentrations were determined using Inductively Coupled Plasma–Mass Spectrometry, and recovery potential was assessed using the Outlook Coefficient and the relative proportion of critical REEs. The results showed that REEs concentrations in AMD water were low, ranging from 0.0005 to 0.449 ppm, with PIT 1 exhibiting the highest concentration under strongly acidic conditions. However, sludge samples exhibited considerable REEs enrichment with total concentrations of 178.13 ppm and 59.09 ppm at the inlet and outlet of the sedimentation pond, respectively. The preliminary outlook analysis showed low potential for direct recovery of REEs from AMD water, but sedimentation pond sludge, especially at the outlet, showed a promising outlook due to its combined high total REEs concentration and high critical content. This study showed that REEs can be recovered and concentrated in solid phases of AMD treatment systems. In addition, the sludge was a more viable and environmentally friendly secondary source.